Development of Implementation Si-Kemal System at Harbormaster and Port Authority Office of Class II Cirebon - Mustain, Iing; Herlina, Yeyen Herlina; Elis Suswati; Eko Wiyandi; Rudy Juanto; Irwan Jaya (Nama Jurnal Akmi, 2026)
A sailing period is needed to improve the profession of seafarers, based on seafarers’ experience, proven during sailing, and to help determine seafarers’ levels. The sea time required by maritime authorities to issue or upgrade professional seafaring licenses. Purpose – The purpose of the study is to develop a sea time information system of professional seafaring that it can provide efficient, simple, and integrated services in supporting the performance of port services at KSOP Class II Cirebon. Methodology – The research method uses an applied approach, where the procedures and stages of making sea service letter are documented, and the resulting activities and plans are presented as menus and access pages for users. Findings – The results of the study were obtained by the development of the sailing period information system at KSOP Class II Cirebon are divided into six activities. The implementation of the Si-Kemal system includes a list of menus and how to use them. The user menu contains user accounts and profiles. While other menus include the sailing experience page, the sailing period SK page. The final stage is data reporting. This report can be sorted by start and end date, which is usually for monthly and yearly reports. Originality – The stages of making a sail period certificate through validation stages 1 and 2 provided by the system, numbering and issuing a Certificate.